NEW DATA ON THE STRUCTURE OF THE OFFSHORE MARGIN OF THE NORTHERN SAKHALIN - Vladimir L. Lomtev; Anna V. Litvinova (Геодинамика и тектонофизика)
This publication presents new data obtained with CDP, gravimetry and magnetometry methods, showing the structure of the offshore margin of the Northern Sakhalin further from the Okhinsky bridge and the Schmidt peninsula, and results of geological interpretation of these data. The study coves: 1) The Trekhbratskaya anticline zone and the megadyke with the same name; 2) The EastSakhalin trough filled in with the Late Cenozoic, mainly the Pomyrskie and Deryuginskie sediments, debris from the Amur river and products of abrasion which occurs at offshore folded structures / bench; 3) The nearbottom gas hydrates and indicators of gas saturation of the Pomyrskie and Deryuginskie sediments. New problems were identified concerning tectonic, magmatic and sedimentation history of the offshore margin and the adjacent structures of the Sakhalin cordillera and the bathyal Deryugin basin.